Pengaruh Efektivitas Work From Home terhadap Kinerja Karyawan dalam Issue Covid-19 pada Dinas Lingkungan Hidup Provinsi Jawa Barat - Sendi Sanjaya Wanah Heryeni; Sri Suwarsi (Bandung Conference Series: Business and Management, 2023)
Abstract. Since the outbreak of Covid-19 in Wuhan in early 2020, the excitement began to spread gradually, even reaching the whole world. This uproar was triggered by the large number of victims in a relatively short time accompanied by the uncertainty of all parties dealing with Covid-19. Various countries then began to implement the Covid-19 Protocol in accordance with the recommendations of the World Health Organization (WHO), including limiting leaving the house and even carrying out isolation measures starting from independent isolation of individuals, communities, and even entire cities. As a result, many offices, both government and private, have implemented the Working from Home/WFH scheme.The purpose of this study was to find out how the effectiveness of work from home at the West Java Environmental Service on the covid 19 issue, to find out how the level of employee performance at the West Java Environmental Service in the covid 19 issue and to determine the effect of the effectiveness of work from home on employee performance levels. on the covid 19 issue at the West Java Environmental Service. The research method used is the survey method. This type of research The research method used is a survey method. The type of research carried out is quantitative verification. The sampling technique used is simple random sampling. The sample in this study were 61 employees of the State Civil Apparatus of the Environmental Service of West Java Province. The data collection technique used is a questionnaire. The data analysis method used is Simple Linear Regression Analysis to determine the data analysis used by the independent variable and the dependent variable. The results of this test state that (1) the work from home effectiveness product variable is in the Good category. (2) Employee performance variables in the Good category. (3) partially the effectiveness of work from home variables has a significant effect on performance variables on employees of the West Java Province Environmental Service. Abstrak. Sejak merebaknya Covid-19 di Wuhan pada awal tahun 2020, kehebohan mulai menyeruak secara berangsur yang bahkan menjangkau seluruh dunia. Kehebohan ini dipicu oleh banyaknya jumlah korban dalam waktu relatif singkat disertai kegamangan semua pihak menghadapi Covid-19. Berbagai negara kemudian mulai menerapkan Protokol Covid-19 sesuai dengan anjuran World Health Organization (WHO), diantaranya membatasi keluar rumah bahkan dilakukan langkah isolasi mulai isolasi mandiri perorangan, komunitas, bahkan seluruh kota. Sebagai akibatnya banyak kantor baik pemerintah maupun swasta yang kemudian menerapkan skema Working from Home/WFH. Tujuan Penelitian ini adalah untuk mengetahui bagaimana efektivitas work from home di Dinas Lingkungan Hidup Jawa Barat pada issue covid 19, untuk mengetahui bagaimana tingkat kinerja karyawan di Dinas Lingkungan Hidup Jawa Barat dalam issue covid 19 dan untuk mengetahui pengaruh efektivitas work from home terhadap tingkat kinerja karyawan pada issue covid 19 di Dinas Lingkungan Hidup Jawa Barat. Metode penelitian yang digunakan adalah metode survey. Jenis penelitian yang Metode penelitian yang digunakan adalah metode survey. Jenis penelitian yang dilaksanakan bersifat kuantitatif verifikatif. Teknik pengambilan sampel yang digunakan adalah simple random sampling. Sampel dalam penelitian ini adalah 61 orang pegawai Aparatur Sipil Negara Dinas Lingkungan Hidup Provinsi Jawa Barat. Teknik pengumpulan data yang digunakan adalah kuesioner. Metode analisis data yang digunakan adalah Analisis Regresi Linier Sederhana untuk mengetahui analisis data yang digunakan variabel independen dengan variabel dependen. Hasil pengujian ini menyatakan bahwa (1) variabel produk efektivitas work from home dalam kategori Baik. (2) Variabel kinerja karyawan dalam kategori Baik. (3) secara parsial variabel efektivitas work from home berpengaruh signifikan terhadap variabel kinerja pada karyawan Dinas Lingkungan Hidup Provinsi Jawa Barat.